Parasites, Pussycats and Psychosis The Unknown Dangers of Human Toxoplasmosis - Torrey, E. Fuller (Springer Nature, 2022)
This open access book analyzes the evidence linking Toxoplasma gondii to the increasing incidence of schizophrenia and bipolar disorder in the United States. Initially establishing that infectious agents are regularly transmitted from animals to humans, lead to human disease, and that infectious agents can cause psychosis, it then examines the protozoan parasite Toxoplasma gondii in detail. Infecting 40 million Americans, Toxoplasma gondii is known to cause congenital infections, eye disease, and encephalitis for individuals who are immunosuppressed. It has also been shown to change the behavior of nonhuman mammals, as well as to alter some personality traits in humans. After discussing the clinical evidence linking Toxoplasma gondii to human psychosis, the book elucidates the epidemiological evidence further supporting this linkage; including the proportional increase in incidence of human psychosis as cats transitioned to domestication over 800 years. Finally, the book assesses the magnitude of the problem and suggests solutions. Parasites, Pussycats and Psychosis: The Unknown Dangers of Human Toxoplasmosis provides a comprehensive review of the evidence linking human psychosis in the United States to infections of Toxoplasma gondii. It will be of interest to infectious disease specialists, general practitioners, scientists, historians, and cat-lovers.